Soda Molek: Efektifitas Pelayanan Publik Di Kelurahan Naikoten II Kecamatan Kota Raja Kota Kupang - Christo Vorando Amalo (Jurnal Inovasi Kebijakan, 2019)
In order to support good governance, it is necessary to innovate public services as a space for the Government to improve the service system that has been inadequate. For this reason, Naikoten II launched a public service innovation program called SODA MOLEK. The purpose of this study is to find out the effectiveness of public services by using the SODA MOLEK application in Naikoten II, also to collect the data and information needed related to factors that affect its effectiveness. The technique of determining the sample is purposive sampling. The location of the study was conducted in the Regional Head Office of Naikoten II, Kota Raja Sub-District, Kupang City. The research was conducted with a qualitative approach, and the type of research is a case study. The results showed that, in general, public services using SODA MOLEK were very effective. This is influenced by the availability of human resources, the discipline of civil servants, the commitment of public services, and the support of Stakeholders, as well as the support of infrastructure and budgets.